2015
DOI: 10.1186/s12864-015-1799-3
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq for gene identification and transcript profiling in relation to root growth of bermudagrass (Cynodon dactylon) under salinity stress

Abstract: BackgroundSoil salinity is one of the most significant abiotic stresses affecting plant shoots and roots growth. The adjustment of root architecture to spatio-temporal heterogeneity in salinity is particularly critical for plant growth and survival. Bermudagrass (Cynodon dactylon) is a widely used turf and forage perennial grass with a high degree of salinity tolerance. Salinity appears to stimulate the growth of roots and decrease their mortality in tolerant bermudagrass. To estimate a broad spectrum of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 60 publications
2
60
0
Order By: Relevance
“…Transcriptomic analysis has been widely used in other grasses, especially in herbaceous plants where genome sequence information is lacking, such as Bermuda grass (Hu et al . ), rye‐grass (Duhoux et al . ) and goose‐grass (An et al .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis has been widely used in other grasses, especially in herbaceous plants where genome sequence information is lacking, such as Bermuda grass (Hu et al . ), rye‐grass (Duhoux et al . ) and goose‐grass (An et al .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomes of maize roots under Na 2 CO 3 treatment (Zhang L.M. et al, 2013), oilseed rape roots under NaCl treatment (Yong et al, 2014), and bermudagrass roots under NaCl treatment (Hu et al, 2015) also showed an enrichment in the “phenylpropanoid biosynthesis” pathway. These results suggest “phenylpropanoid biosynthesis” pathway might play an important role in plant response to alkalinity and salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Protoplast transformation may be another choice under the precondition of the implementation of the protoplast regeneration. With the great progress in next-generation sequencing, large amounts of transcriptomics and proteomics statistical data related to bermudagrass resistance to low temperature [8,9,52], drought [83,84] and salt stress [85][86][87], have been published. We can take full advantage of these data for studying the molecular mechanism of bermudagrass resistance and resistance breeding.…”
Section: Prospectsmentioning
confidence: 99%